2011
DOI: 10.1016/j.schres.2011.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Long acting injection versus oral risperidone in first-episode schizophrenia: Differential impact on white matter myelination trajectory

Abstract: Context Imaging and post-mortem studies provide converging evidence that subjects with schizophrenia (SZ) have a dysregulated trajectory of frontal lobe myelination. Prior MRI studies suggested that early in treatment of SZ, antipsychotic medications initially increase frontal lobe white matter (WM) volume, which subsequently declines prematurely in chronic stages of the disease. Insofar as the trajectory of WM decline associated with chronic disease may be due to medication non-adherence, it may be modifiable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 46 publications
2
65
0
Order By: Relevance
“…A positive answer for benefits on disease progression would provide support to an emerging literature regarding the neuroprotective effects of APs, especially SGAs [Bartzokis et al 2011;Gassó et al 2010].…”
Section: Guidelines and Recommendations For The Treatment Of Schizophmentioning
confidence: 87%
“…A positive answer for benefits on disease progression would provide support to an emerging literature regarding the neuroprotective effects of APs, especially SGAs [Bartzokis et al 2011;Gassó et al 2010].…”
Section: Guidelines and Recommendations For The Treatment Of Schizophmentioning
confidence: 87%
“…However, this practice is not evidence based and there are anecdotal reports that LAIs may be of particular value when used early in the course of illness 16, 23, 26, 27, 28, 29, 30. Recently, a few randomized studies have demonstrated the value of using APs early in the course of schizophrenia 31, 32.…”
Section: Discussionmentioning
confidence: 99%
“…Improving adherence seems to be particularly important early on in the disease, with greater improvement in clinical outcomes in patients treated with risperidone LAI (RLAI) who were recently diagnosed with schizophrenia than in those with chronic schizophrenia (Olivares et al, 2009). Otherwise, recent studies demonstrated the superiority of RLAI, compared with the oral form, to maintain frontal lobe myelinization, to increase frontal lobe intracortical myelin, and to improve cognitive performance in the first psychotic episode (Bartzokis et al, 2011(Bartzokis et al, , 2012.…”
Section: Reasons For Nonuse Of Depot Medicationmentioning
confidence: 99%